Raising Healthy Children: Go, Slow, Whoa - Rebecca A. Clinton; Karla P. Shelnutt (EDIS, 2010)
FCS8921, a 4-page illustrated fact sheet by Rebecca A. Clinton and Karla P. Shelnutt, introduce families to Go, Slow, Whoa, a research-based tool developed by the National Institutes of Health and the Coordinated Approach to Child Health (CATCH) program to help individuals identify foods that are lower in fat and calories. Published by the UF Department of Family Youth and Community Sciences, June 2010.